Turk Arch Pediatrics 2022
DOI: 10.5152/turkarchpediatr.2022.21309
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Impact of Environmental Changes on Asthma Control in Children, Access to Health Care, and Treatment Adherence in Early COVID-19 Lockdown

Abstract: Objective : During the coronavirus disease 2019 pandemic, lockdown measures and difficulties in accessing healthcare have impacted asthma management in children. This study aimed to determine the evaluation of the impact of environmental changes on asthma control in children, access to health care, and treatment adherence in early coronavirus disease 2019 lockdown. Materials and Methods: The study included children with asthma aged 6-11 years. A survey form was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…A quantitative synthesis was not possible for these additional endpoints due to the low number of studies examining each outcome or the different definitions used across the included studies. However, the overall direction of the effects was the same for asthma symptoms and asthma‐related quality of life, as an overall improvement in asthma symptoms and asthma severity during lockdown was reported in all studies that addressed these endpoints 41,45,48 . A similar result was obtained by Feldman et al, who assessed asthma‐related quality of life using the Pediatric Asthma Caregiver's Quality of Life Questionnaire (PACQLQ).…”
Section: Resultssupporting
confidence: 65%
See 4 more Smart Citations
“…A quantitative synthesis was not possible for these additional endpoints due to the low number of studies examining each outcome or the different definitions used across the included studies. However, the overall direction of the effects was the same for asthma symptoms and asthma‐related quality of life, as an overall improvement in asthma symptoms and asthma severity during lockdown was reported in all studies that addressed these endpoints 41,45,48 . A similar result was obtained by Feldman et al, who assessed asthma‐related quality of life using the Pediatric Asthma Caregiver's Quality of Life Questionnaire (PACQLQ).…”
Section: Resultssupporting
confidence: 65%
“…Asthma symptom control was more frequently quantified using the c‐ACT score, 31,38,40,42–48 while in the remaining studies, asthma symptom control was quantified using the Global Initiative for Asthma score 39,43,45 . Differences in asthma control before and during lockdown periods were also quantified through changes in exacerbation frequency 39,43–45 and in symptom severity 41,48 . Among the nine studies assessing asthma symptom control directly, three reported changes in the mean level of asthma symptom control 31,38,48 and were included in the SMD meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations